REVIEW of the scientific article Yaryna Bohiv “Harmonization of International Standards and the National Legal System Regarding the Institutional Development of Civil Society Entities” - Kharkivska, Kateryna (Global Prosperity, 2023)
REVIEW of the scientific article Yaryna Bohiv “Harmonization of International Standards and the National Legal System Regarding the Institutional Development of Civil Society Entities”